Pregnancy-associated stroke -a systematic review of subsequent pregnancies and maternal health - Liisa Karjalainen; Minna Tikkanen; Kirsi Rantanen; Hannele Laivuori; Mika Gissler; Petra Ijäs (BMC, 2019)
Abstract Background Pregnancy-associated stroke is a rare but life-threatening event, with an estimated incidence of 30/100000 deliveries. Data on the risk of stroke recurrence and the risk of other adverse pregnancy outcomes are essential for adequate counselling and surveillance in subsequent pregnancies. The aim of this systematic review is to describe the implications of a pregnancy-associated stroke for the future health of these women. Methods We searched Ovid Medline, PubMed, Cochrane Library and CINAHL for articles published in 1980-2018. Articles including women with pregnancy-associated stroke and information on at least one of the following outcomes were included: 1) recurrence of stroke during subsequent pregnancy, 2) number and course of subsequent pregnancies and their outcomes and 3) subsequent cardiovascular health. Results Twelve articles were included in the review, with six providing information on subsequent pregnancies, four on subsequent maternal health and two on both. The included articles varied greatly in terms of study design, length of follow up and reported outcomes. We found 252 women with pregnancy-associated stroke for whom the outcomes of interest were reported: 135 women with information on subsequent pregnancies and 123 women with information on future health. In total, 55 pregnancies after stroke were found. In the majority of studies, the incidence of pregnancy complications was comparable to that of the general population. The risk of stroke recurrence during pregnancy was 2%. Data on subsequent health of these women were limited, and the quality of the data varied between the studies. Conclusions Data on subsequent pregnancies and health of women with a history of pregnancy-associated stroke are limited. Further research on this topic is essential for adequate counselling and secondary prevention.